Investigating factors that improve golf scores by comparing statistics of amateur golfers in repeat scramble strokes and one-ball conditions - Suzuki, T.; Sheahan, J. P.; Okuda, I.; Ichikawa, D. (Journal of Human Sport & Exercise, 2021)
This study investigated how scores and statistics of amateur golfers changed when self-scramble (SC) was compared to normal play. Participants took two (SC2) to three (SC3) golf strokes each. Scores under these conditions were compared with those from normal round (NR) play to determine to what extent the scores and statistics would improve. Means, standard deviations, repeated measures one-way ANOVA, and a forward stepwise multiple regression analysis were performed for data analysis. The mean total score over nine holes by NR plays was 46.6 strokes, with a significant reduction of 7.7 strokes and 10.6 strokes under SC2 and SC3 conditions, respectively. Even when the three play conditions` total scores decreased significantly for all subjects, the putt rate was around 38%, suggesting that the ratio of the number of putts per score did not change when play conditions changed. Stepwise multiple regression analysis for NR and SC2 using total score as the dependent variable and each statistic as the independent variables showed that greens in regulation (GIR) predicted 51.2% of the total score for NR; GIR and the One-Putt rate predicted 87.3% of the total score for SC2. These findings indicate that GIR is the most important factor for reducing non-professional golfers` total scores. This study suggests that players gain experience in reducing their golf scores in a format that is similar to an actual game of golf.